2023
DOI: 10.3390/microorganisms11071652
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in the Use of Probiotics to Improve Meat Quality of Small Ruminants: A Review

Abstract: Meat from small ruminants is considered a high quality and delicacy product in many countries. Several benefits have been perceived from probiotics as dietary supplements, such as improved carcass weight, color, tenderness, flavor, muscle fiber structure, water-holding capacity, and healthy fatty acid profile of the meat. Thus, the present review focuses on the effect of probiotics on improving the quality of meat from small ruminants. Though many benefits have been associated with the use of probiotics, the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 68 publications
0
3
0
Order By: Relevance
“…Information for each source was collated considering the probiotics, experimental mode, animal, time, weight growth, free fatty acid/glycerides/cholesterol, anti-inflammatory adipokines, and pro-inflammatory adipokines. The documents were selected based on the criteria listed in Figure 1 according to Saha et al (2023) [19].…”
Section: Methodsmentioning
confidence: 99%
“…Information for each source was collated considering the probiotics, experimental mode, animal, time, weight growth, free fatty acid/glycerides/cholesterol, anti-inflammatory adipokines, and pro-inflammatory adipokines. The documents were selected based on the criteria listed in Figure 1 according to Saha et al (2023) [19].…”
Section: Methodsmentioning
confidence: 99%
“…Thus, the use of antibiotics has been banned in many regions of the world, such as the European Union in 2006 (Chen et al, 2005) or its use has been limited in many countries such as USA, Japan, and China. In order to reduce the use of antimicrobials in livestock, several alternatives are being explored, including the use of immunomodulatory probiotics (immunobiotics) (Villena et al, 2018;Saha et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is necessary to search for the most effective probiotic communities for raising animals. S. Saha et al (2023) showed that the addition of probiotics to rabbits' diets helped increase carcass weight, improve colour, muscle fibre structure, and taste. Studies do not provide information on the properties of probiotic strains, their dosage, administration method and mechanism of use.…”
Section: Introductionmentioning
confidence: 99%